Core-shell structured gold nanoparticles as carrier for 166Dy/166Ho in vivo generator - Runze Wang; Bernard Ponsard; Hubert Wolterbeek; Antonia Denkova (SpringerOpen, 2022)
Abstract Background Radionuclide therapy (RNT) has become a very important treatment modality for cancer nowadays. Comparing with other cancer treatment options, sufficient efficacy could be achieved in RNT with lower toxicity. β− emitters are frequently used in RNT due to the long tissue penetration depth of the β− particles. The dysprosium-166/holmium-166 (166Dy/166Ho) in vivo generator shows great potential for treating large malignancies due to the long half-life time of the mother nuclide 166Dy and the emission of high energy β− from the daughter nuclide 166Ho. However, the internal conversion occurring after β− decay from 166Dy to 166Ho could cause the release of about 72% of 166Ho when 166Dy is bound to conventional chelators. The aim of this study is to develop a nanoparticle based carrier for 166Dy/166Ho in vivo generator such that the loss of the daughter nuclide 166Ho induced by internal conversion is prevented. To achieve this goal, we radiolabelled platinum-gold bimetallic nanoparticles (PtAuNPs) and core-shell structured gold nanoparticles (AuNPs) with 166Dy and studied the retention of both 166Dy and 166Ho under various conditions. Results The 166Dy was co-reduced with gold and platinum precursor to form the 166DyAu@AuNPs and 166DyPtAuNPs. The 166Dy radiolabelling efficiency was determined to be 60% and 70% for the two types of nanoparticles respectively. The retention of 166Dy and 166Ho were tested in MiliQ water or 2.5 mM DTPA for a period of 72 h. In both cases, more than 90% of both 166Dy and 166Ho was retained. The results show that the incorporation of 166Dy in AuNPs can prevent the escape of 166Ho released due to internal conversion. Conclusion We developed a chelator-free radiolabelling method for 166Dy with good radiolabelling efficiency and very high stability and retention of the daughter nuclide 166Ho. The results from this study indicate that to avoid the loss of the daughter radionuclides by internal conversion, carriers composed of electron-rich materials should be used.